Peran Gojek Sebagai Akses Publik Wisatawan di Bali dan Pelopor Ekonomi Kreatif - Dewantara, Made Handijaya (JURNAL MASTER PARIWISATA; Volume 06, Nomor 01, Juli 2019DO - 10.24843/JUMPA.2019.v06.i01.p08, 2019)
This study aims to understand the position of Gojek as public access to tourists when traveling in Bali, by looking at the positioning strategy of Gojek as an innovative model for online platform in the field of transportation services, as well as one of the alternative solutions for tourism accessibility, which can be beneficial in sustainable tourism in Bali. The research was conducted through in-depth interviews and in-depth observation. Through the research conducted, it can be concluded that the Gojek application as an online application based on transportation and public access has a significant role in the tourism industry in Bali. As the first decacorn in Indonesia, Gojek has demonstrated its commitment to fulfill the satisfaction of all the needs and desires of customers with requests that change from time to time, especially for those who have activities in Bali. This was demonstrated through various application variants released by Gojek as a start-up company. By understanding the needs and desires of tourists vacationing in Bali, Gojek can understand the behavior of consumers who use services again continuously which will lead to customer loyalty. Gojek also provides important positioning through their marketing strategies. As a transportation-based application, Gojek also make partners with local entrepreneurs who can generate creativity and a shared economy model. This creation is demonstrated through innovation and creativity and business that provides many job opportunities for Gojek partners. The reliability of Gojek in their marketing strategy is demonstrated through their seven-marketing mix. Keywords: transportation, innovation, creativity, accessibility.